Technology for magnesium castings : design, products & applications. - Sahoo, Mahi (American Foundry Society, 2011)
The latest casting and processing technologies have raised the importance of magnesium in the transportation industry. As a structural material with low density and a very high strength-to-weight ratio, magnesium can reduce vehicle weight and, in turn, reduce greenhouse gas emissions and increase fuel economy. This book provides valuable information on: melt control process control casting and solidification heat treatment materials selection various casting processes.